Uporabe metode glavnih komponent pri klasifikaciji tumorjev - Pleško, Ema (Matrika, 2020)
The article describes one of the various possibilities of using principal component analysis - PCA in biotechnological context. Firstly there is a short presentation of PCA method in more general terms, followed up with presentation of a research that actually applied PCA for tumour analysis based on data collected from cancer cell lines. At the end of the article there is a simple hand-on implementation of the pca in famous iris dataset. The implementation highlights the usefulness of the PCA.
Keywords: klasifikacija tumorjev; metoda glavnih komponent; oncology; onkologija; principal component analysis; tumor classification